2021
DOI: 10.1016/j.proci.2020.06.136
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of lean blow out performance of spray and premixed swirled flames using nanosecond repetitively pulsed discharges

Abstract: Plasma-Assisted Combustion (PAC) has shown potential in improving the ignition, extinction, and dynamic performance of combustion systems. In this work, Nanosecond Repetitively Pulsed (NRP) spark discharges are applied to extend the lean blow out limit of the SICCA-Spray burner. This laboratory-scale atmospheric test rig is equipped with a swirl spray injector representing in an idealized fashion a single sector of a gas turbine. Three fuels and injection conditions are considered: perfectly premixed methane-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…This can be done either by limiting the pulse duration, such as in spark NRPD [174], or by specific electrode arrangements, such as in gliding arcs [189]. Different enhancement strategies have been successfully tested, for examples spark NRPD applied locally in the burnt gases of recirculation zones [152,193], spark NRPD applied locally in the flammable mixture [179], or spark NRPD and gliding arcs distributed in the flammable mixture [174,189]. Figure 22 shows an example of spark NRPD distributed at the outlet of the injection tube of a swirl combustor (Adapted from [171]).…”
Section: Thermal Effectmentioning
confidence: 99%
“…This can be done either by limiting the pulse duration, such as in spark NRPD [174], or by specific electrode arrangements, such as in gliding arcs [189]. Different enhancement strategies have been successfully tested, for examples spark NRPD applied locally in the burnt gases of recirculation zones [152,193], spark NRPD applied locally in the flammable mixture [179], or spark NRPD and gliding arcs distributed in the flammable mixture [174,189]. Figure 22 shows an example of spark NRPD distributed at the outlet of the injection tube of a swirl combustor (Adapted from [171]).…”
Section: Thermal Effectmentioning
confidence: 99%
“…Optimal discharge placement was studied by Kim et al [25], but the conclusions of this study performed in a non-premixed configuration are not relevant for the present work which is conducted with a premixed flame. In recent work with liquid fuels, Vignat et al [8] showed that the electrode position has a significant impact on the lean blow-out performance in a swirl-stabilized combustor. They found that the discharge was more efficient in the outer recirculation zone than close to the injector.…”
Section: A Discharge Positionmentioning
confidence: 99%
“…Plasma effects on combustion gas mixture are carefully studied for many years. Several works have shown a significant lean blow out limit extension using Nanosecond Repetitively Pulsed (NRP) discharges in premixed flames [4]- [7] for different fuels [8]. The ignition probability is higher and the performances are better than with conventional spark discharges [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…An emerging solution to enable flame stabilization, suitable to a wide range of combustion applications, is to locally generate a plasma [2,3]. Among the various possible types of discharges to enhance combustion [4,5], the Nanosecond Repetitively Pulsed (NRP) discharges [6] succeeded to stabilize ultra-lean premixed flames on several laboratory-scale hydrocarbon-air flames [6,7] but also in test rigs representative of a gas turbine environment at atmospheric [8,9] and high pressure [10,11]. This technique is very efficient because the energy consumption of the plasma is typically less than 1% of the power released by the flame.…”
Section: Introductionmentioning
confidence: 99%